2022
DOI: 10.1186/s12889-022-14334-y
|View full text |Cite
|
Sign up to set email alerts
|

International medical students’ acculturation and self-rated health status in Hungary: a cross-sectional study

Abstract: Background Over the past few decades, the number of international students has increased dramatically. These students have to adjust to unfamiliar social, cultural, and educational environments. The concept of acculturation has been applied in multiple studies on various health outcomes. This study investigated the relationship between acculturation and self-rated health (SRH) among international medical students. Methods A cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, another study claims that only students with symptoms of the disease at a severe stage would come to seek medical assistance [ 7 , 31 ]. When analysing between local and international students, there may be several things that need to be considered, as it is known in the previous research that the mental health of international students might be influenced by the process of acculturation that they experience [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study claims that only students with symptoms of the disease at a severe stage would come to seek medical assistance [ 7 , 31 ]. When analysing between local and international students, there may be several things that need to be considered, as it is known in the previous research that the mental health of international students might be influenced by the process of acculturation that they experience [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted in Hungary [ 10 ], Hungarian students reported less mental well-being than students from the Mediterranean region, Israel, and Scandinavia. Furthermore, it was discovered that 49.7% of foreign students in Hungary who self-reported their mental health had poor mental health [ 11 ]. Meanwhile, the chronic disease burden is increasing globally.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study claims that only students with symptoms of the disease at a severe stage would come to seek medical assistance [7,20]. When analysing between local and international students, there may be several things that need to be considered, as it is known in the previous research that the mental health of international students might be in uenced by the process of acculturation that they experience [21].…”
Section: Main Ndingsmentioning
confidence: 99%
“…Besides the common-shared burdens that domestic and international university students have faced during the pandemic, international students additionally faced the challenges of adapting to living in a new country, with its new social, cultural, and educational aspects. High levels of acculturative stress and difficulties in adjusting to the host country have been reported even before the COVID-19 pandemic [ 5 , 16 ]. Therefore, social distancing and isolation experienced by the students due to the host country government’s restriction measures during the pandemic might have had even larger negative effects on their mental health than on their domestic counterparts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%